Financial accounting fundamentals - Wild, John J. (McGraw-Hill/Irwin, 2007)
Wild's Financial Accounting Fundamentals responds to the market's request for a low-cost, succinct book; a book that balances large and small businesses, and one that is contemporary, engaging, and accessible for todayýs students. With numerous innovative features,...